The Analysis Role of Profitability as Moderating Variable in Relationship Between Free Cash Flow, Managerial Ownership, Dividend Policy and Opportunity Investment - Prety Diawati; Pius Weraman; Rina Destiana; Muhammad Amsal Nasution; Abdurohim Abdurohim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
With profitability acting as a moderator, the goal of this study was to ascertain the impact of managerial ownerships, free cash flow, and investment opportunities on dividend policy. For this study, the sample of manufacturing firms listed on the Stock Exchange between 2013 and 2017 was used. This study used 12 firms as its sample during a five-year period, making up a total of 60 companies. Purposive sampling is the technique employed. In this study, multiple regression was used to test the hypothesis and SPSS was used to determine the value of the absolute difference. The study's findings indicated that while managerial ownerships and the setting of investment opportunities don't have an impact on dividend policy, free cash flow does. Profitability isn't important when free cash flow, managerial ownerships, and investment opportunities are tempered by dividend policies.